2020
DOI: 10.18502/jfrh.v14i3.4668
|View full text |Cite
|
Sign up to set email alerts
|

Supplement Usage Pattern in a Group of COVID- 19 Patients in Tehran

Abstract: Objective: The coronavirus disease 19 (COVID-19) is a highly transmittable and pathogenic viral infection, causes severe acute respiratory syndrome and was spread throughout the world in early 2020. The effects of vitamin and micronutrient supplements on the prevention and treatment of COVID- 19 seems challenging in scientific considerations. On the other side generally, experts warn against over-consumption of these supplements. Materials and methods: This study aimed to investigate the vitamin and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…Interestingly, Puścion-Jakubik et al demonstrated that a significantly greater percentage of Polish respondents declared not taking food supplements with zinc and vitamin D during the first wave of the COVID-19 pandemic [26]. In many countries, an evaluated interest in diet supplementation during the COVID-19 pandemic was found [27][28][29]. Our results demonstrate higher intake of vitamin D by women than by men.…”
Section: Discussionmentioning
confidence: 43%
“…Interestingly, Puścion-Jakubik et al demonstrated that a significantly greater percentage of Polish respondents declared not taking food supplements with zinc and vitamin D during the first wave of the COVID-19 pandemic [26]. In many countries, an evaluated interest in diet supplementation during the COVID-19 pandemic was found [27][28][29]. Our results demonstrate higher intake of vitamin D by women than by men.…”
Section: Discussionmentioning
confidence: 43%
“…The other study had a quasi-experimental design and indicated that vitamin D3 supplementation was inversely associated with Ordinal Scale for Clinical Improvement (OSCI) score for COVID-19 (β = −3.84; 95% CI: −6.07, −1.62; P = 0.001) ( 56 ). The third study, which assessed vitamin D supplementation in patients with a past history of COVID-19, found that it reduces the risk of exacerbation and worsening of the disease (OR: 0.29; 95% CI: 0.10, 0.083; P = 0.02) ( 57 ). The last study did not provide sufficient data, and only reported that VDD was significantly associated with severity; however, no data were available to indicate this ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…A significant association between VDD and risk of hospitalization was observed in Radujkovic et al ( 13 ) (31% hospitalization in VDD vs. 69% in non-VDD, P = 0.004) and a marginally significant relation in Merzon et al ( 40 ) (adjusted OR: 1.95; 95% CI: 0.98, 4.845; P = 0.06). The third study was a cross-sectional study that compared history of vitamin D3 supplement intake between inpatients and outpatients ( 57 ), where vitamin D3 intake was reported in 30% of outpatients versus 16.5% of hospitalized patients ( P = 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a relevant difference was found considering zinc intake-9% vs. 2% in outpatients and inpatients, respectively. However, none of the patients declared the usage of multivitamins, vitamin C, vitamin E, folic acid, iron, omega-3, and omega-6 fatty acids [21]. In this research, none of the participants had COVID-19 in the first wave, 11.8% in the second, and 17.6% in the third waves; 14%, 28.3%, and 33.7% of respondents could not equivocally say whether they had SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%